Desirability of immediate surgical standby for coronary angioplasty. - Levy, R D (1991)
OBJECTIVE--To assess the value of emergency surgical standby for percutaneous transluminal coronary angioplasty. DESIGN--Retrospective review of the major complications of coronary angioplasty in a regional cardiac centre. SETTING--All angioplasties were performed in the cardiac catheterisation laboratory of Wythenshawe Hospital with surgical standby in an adjoining operating theatre. PATIENTS--1262 vessels were dilated in 1032 patients (mean age 53 years) between 1984 and 1989. MAIN OUTCOME MEASURES--In-hospital mortality from emergency surgical revascularisation after angioplasty; the rate of myocardial infarction and overall morbidity. RESULTS--Coronary angioplasty achieved primary success in 90% of cases. Thirty eight (3.7%) patients (five women (mean age 55.8) and 33 men (mean age 53.0] were referred for urgent surgical revascularisation--36 direct to operation and two within 24 hours. All patients survived surgery. Five of the 38 had had a previous angioplasty to the same vessel and one had had previous coronary artery grafts. Four of the 38 had an angioplasty for unstable angina. Eighteen had single, 13 double, and seven triple vessel coronary artery disease. The target vessel was the left anterior descending in 25, right coronary artery in nine, circumflex in three, and the left anterior descending and circumflex coronary arteries in one. Five required external cardiac massage on the way to the operating theatre; two of them had a left main stem occlusion. Four internal mammary artery and 60 reversed saphenous vein grafts were implanted (1.6 per patient). Complete revascularisation was achieved in 36 (94.7%) patients. Q wave myocardial infarction occurred in six (15.8%). The final outcome was: none dead, three patients with angina, one late death, one cerebrovascular accident, one late operation for a new left anterior descending lesion, two patients on diuretics with or without an angiotensin converting enzyme inhibitor. One orthotopic transplant was performed in a patient in whom cardiogenic shock developed after the left anterior descending coronary artery became occluded 72 hours after angioplasty. CONCLUSION--There was no surgical mortality and low morbidity among patients for whom immediate surgical cover was requested.